The Qur’an and the Sunnah on Violence, Armed Struggle, and the Political Process (American Journal of Islam and Society, 1991)
TranslationIn the name of Allah, Most Gmcious,Most Merciful.1. To those against whomWar is made, permissionis given (to fight), becauseThey are wronged-and verily,Allah is Most PowerfulFor their aid-(They are) those who haveBeen expelled from their homesIn defiance of right-(For no cause) exceptThat they say, “Our LordIs Allah.“ Did not AllahCheck one set of peopleBy means of anotherThere would surely have beenPulled down monasteries, churches,Synagogues, and mosques, in whichThe name of Allah is commemoratedIn abundant measure. Allah willCertainly aid those whoAid His (cause)-for verilyAllah is Full of Strength,Exalted in Might,(Able to enforce His Will).Al Hajj {22:39-40)2. Fight in the cause of AllahThose who fight you,But do not transgress limits;For Allah loveth not transgressors.And slay themWherever ye catch them,And turn them outFrom where they haveTurned you out; ...